2017
DOI: 10.12740/app/67931
|View full text |Cite
|
Sign up to set email alerts
|

Pathological use of mobile phones by secondary school students

Abstract: Aim of the studyThe dangers resulting from the dysfunctional use of mobile phones by adolescents are presented in the study. The main aim of the conducted study was the exploration of addiction to mobile phones used by secondary students as well as the presentation of differences in addiction to mobile phones in group of women and men. 470 Polish secondary students from Silesia took part in the study.Subject or material and methodsThe author’s distributed questionnaire which contained questions concerning the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 18 publications
6
13
2
1
Order By: Relevance
“…This is consistent with an earlier study of Chinese adolescents that found student relationships negatively associated with MPA . Previous studies found that female middle school and university students and younger age had more severe MPA, which was not confirmed in this study.…”
Section: Discussionsupporting
confidence: 75%
“…This is consistent with an earlier study of Chinese adolescents that found student relationships negatively associated with MPA . Previous studies found that female middle school and university students and younger age had more severe MPA, which was not confirmed in this study.…”
Section: Discussionsupporting
confidence: 75%
“…(2019) [54] N = 1041M = 12.4SD = 0.7Female = 44.5%Male = 55.5%ChinaSAS V2Child neglect, psychological abuse, and emotion-focused coping were risk factors for smartphone addictionEmotional intelligence and coping style mediated the relationship between neglect/abuse and addictionWang et al. (2017) [55] N = 768M = 16.8SD = 0.7Female = 56.0%Male = 44.0%ChinaSAS–SVStudents with better student–student relationships were less likely to be addictedStudents with higher self-esteem were less likely to be addictedSelf-esteem was a mediator between student–student relationships and smartphone addictionThis was moderated by the need to belongWarzecha and Pawlak (2017) [56] N = 47016–20 yearsFemale = 61.1%Male = 39.9%PolandKBUTKAround 35% at risk for smartphone addiction; around 4% showed smartphone addictionHigher amount of smartphone addiction and risk for smartphone addiction in girls than in boysYang et al. (2010) [57] N = 11,111M = 14.6SD = 1.7Female = 50.3%Male = 49.7%TaiwanPCPU–Q16.4% had problematic cell phone use, girls more likely than boys<15 years were more likely to show problematic phone useYildiz (2017) [58] N = 262M = 16.6SD = 1.1Female = 50.4%Male = 49.6%TurkeySAS–SVExternal-dysfunctional emotion regulation, internal-dysfunctional emotion regulation, and internal-functional emotion regulation significantly predicted Internet and smartphone addictionEmotion-regulation strategies explained 19% of variance in smartphone addiction N sample size, M mean, SD standard deviation, SAS (V1) Smartphone Addiction Scale – Version 1 ([59], cited by [34]), SAS Smartphone Addiction Scale – Original Version [29], AUSS Addictive Use of Smartphone Scale ([60], cited by [35]), S Scale scale to measure smartphone dependence from the Survey on Internet Overdependence ([61], cited by [13]), SNS social networking services, SAPS Smartphone Addiction Proneness Scale [30], TMD Test of Mobile Phone Dependence [36], SAS–SV Smartphone Addiction Scale—Short Version [10], PMPUS Problematic Mobile Phone Use Scale [62, 63], MPPUS-10 Mobile Phone Prob...…”
Section: Resultsmentioning
confidence: 99%
“…Several studies identified female gender as a risk factor [5, 21, 31, 36, 52, 56], reporting significant positive associations between female gender and problematic usage in adolescents (13–20 years) [10, 18, 37, 47]. Contrary to this, some studies reported smartphone addiction only in boys [28] or found higher scores in boys than in girls [19, 45].…”
Section: Resultsmentioning
confidence: 99%
“…Studies recently found that PMPU has complex negative effects on individuals’ daily lives and may ultimately lead to depression [3], sleep problems [4] and other negative outcomes [5,6]. Therefore, PMPU has increasingly attracted the attention of researchers and social workers [3,7,8,9] and relevant findings have specifically suggested that adolescents are highly susceptible to PMPU [10] due to their immature cognitive regulation capacity and greater time flexibility [11]. For example, a study reported that the prevalence rate of smartphone addiction in Korean adolescents was 11.4% [12].…”
Section: Introductionmentioning
confidence: 99%